2016
DOI: 10.1080/13697137.2016.1249840
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between muscle and bone in postmenopausal women with hypovitaminosis D

Abstract: A low 25-OHD level in postmenopausal women is associated with high body fat, metabolic syndrome, low muscular strength and osteopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“… Non-diabetic subject studies for the medium BMI quartile (25–30): Forest plot shows the correlation between vitamin D status and BMI [ 19 , 21 , 22 , 23 , 29 , 32 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 47 , 49 , 50 , 51 ]. A random effect model was used to calculate the correlations and 95% CI ( I 2 = 64.411%, p = 0.000).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Non-diabetic subject studies for the medium BMI quartile (25–30): Forest plot shows the correlation between vitamin D status and BMI [ 19 , 21 , 22 , 23 , 29 , 32 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 47 , 49 , 50 , 51 ]. A random effect model was used to calculate the correlations and 95% CI ( I 2 = 64.411%, p = 0.000).…”
Section: Figurementioning
confidence: 99%
“… Authors’ assessment of the risk of bias in non-diabetic subject studies: Data shown for each individual study (the plus sign indicates a low risk of bias, the minus sign shows a high risk of bias, and the question mark indicates that the risk of bias is unknown) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. …”
Section: Figurementioning
confidence: 99%
“…However, we have not been able to demonstrate the positive relationship of vitamin D status with physical activity, probably due to low physical activity patterns in our postmenopausal women. Authors like Vuksanovic et al [50] stated that visceral fat is more harmful than subcutaneous fat, emphasizing that women with high amounts of visceral fat have low serum 25(OH)D levels. Therefore, it would be necessary to assess the location of body fat and its influence on vitamin D status for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A associação entre o envelhecimento e a diminuição da força muscular vem sendo estudada a mais de 150 anos. Atualmente, existe o consenso que a diminuição da força se torna mais evidente a partir dos 60 anos, além, de ser mais acentuada no sexo feminino pós-menopausa (PHILLIPS, S. K. et al 1993, VUKSANOVIC, M. et al 2016. De acordo com estudo promovido por Deschenes, a força muscular máxima é alcançada por volta dos 30 anos de idade, mantendo-se mais ou menos estável até à quinta década, idade, a partir da qual, inicia-se o seu declínio.…”
Section: Envelhecimento E Forçaunclassified